The Relationship of Academic Stress to Smoking Behaviour in Students of Faculty of Geological Engineering - Diah, Maya Hanissya; Maulana, Indra; Yamin, Ahmad (GLOBAL HEALTH SCIENCE GROUP, 2024)
The relationship between academic stress coping and smoking behaviour is crucial with the increase of adult smokers in Indonesia, especially among university students, adding urgency to the understanding of the relationship between academic stress and smoking behaviour. Objectives: So this study aims to determine the relationship between academic stress and smoking behaviour in students of the Faculty of Geological Engineering, Padjadjaran University. Methods: The method used in this study is an analytical descriptive design with a cross-sectional approach. The population in this study were active students of the 2020 and 2021 batches of the Faculty of Geological Engineering at Padjadjaran University totalling 259 people. The sample taken using the calculation of proportionate stratified random sampling was 157 students. Data were collected using The Perception of Academic Stress instrument developed by Gabriel and Bedewy (2015) containing 18 statements and Smoking behaviour developed by Komang Yunita (2021) containing 15 statements. Data analysis was carried out with a descriptive statistical approach and the Spearman Rank Correlation test. Results: The results of this study showed a p value> 0.05 (0.061), then H0 was accepted and Ha was rejected. Conclusion: The statement shows there is no significant relationship between academic stress and smoking behaviour but a positive relationship although very weak. Based on varibael, more than half of FTG Unpad students experience academic stress in the moderate category (53.5%) and almost half of students do not smoke (43.3%).